Zera Yacob’s Hatata and the vitality of an Indigenous Ethiopian Philosophy - Merawi, Fasil (Ethiopian Journal of Social Sciences, 2018)
In today’s globalized world, indigenous knowledge is seen as a way of mediating the gap between foreign and local forms of knowledge, envisioning a holistic and sustainable form of development and exploring the wisdom of indigenous cultures. To this extent, it develops a severe critique of programs of modernization and westernization, in return emphasizing the value of artistic, literary, environmental and ethical systems of thought extracted from local communities. Some of the contending labels through which the quest for indigenous knowledge finds expression include indigenous culture, art, environmental ethics, governance, conflict resolution and philosophy. This paper explores primarily the possibility of an indigenous Ethiopian philosophy through an analysis of the ideas of a modern Ethiopian philosopher, Zera Yacob. Animated by the religious controversies and disputes over the nature of true faith in modern Ethiopia, Zera Yacob developed a unique indigenous philosophy in his work- the Hatata. In this work, he grappled with questions of religious disputes and mutual coexistence, the relation between ethics and rationality, the laws of man, reason and God, and social and political issues amongst others. Through an interrogation of Zera Yacob’s Hatata, this paper argues that, (1) Zera Yacob’s philosophy, by developing a system of philosophy guided by the light of reason challenges Western conceptions of Africa and Africans as pre-logical, barbaric and uncivilized, (2) the Hatata introduced a rational foundation for ethics that could be used to analyze everyday moral dilemmas, and (3) the Hatata  emphasized the notion of religious pluralism which could be used to settle religious disputes and controversies at this point in time.